2019
DOI: 10.1371/journal.pone.0209674
|View full text |Cite
|
Sign up to set email alerts
|

Performance of sparse-view CT reconstruction with multi-directional gradient operators

Abstract: To further reduce the noise and artifacts in the reconstructed image of sparse-view CT, we have modified the traditional total variation (TV) methods, which only calculate the gradient variations in x and y directions, and have proposed 8- and 26-directional (the multi-directional) gradient operators for TV calculation to improve the quality of reconstructed images. Different from traditional TV methods, the proposed 8- and 26-directional gradient operators additionally consider the diagonal directions in TV c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Previous studies [3,4] reported that the ITV uses the multidirectional gradient information of pixels and showed that multidirectional ITV could effectively improve imaging accuracy. Inspired by their research, we propose a novel ATV that uses the 8-direction gradient information of a pixel, that is, MATV.…”
Section: Multidirectional Anisotropic Total Variationmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies [3,4] reported that the ITV uses the multidirectional gradient information of pixels and showed that multidirectional ITV could effectively improve imaging accuracy. Inspired by their research, we propose a novel ATV that uses the 8-direction gradient information of a pixel, that is, MATV.…”
Section: Multidirectional Anisotropic Total Variationmentioning
confidence: 99%
“…X-ray computed tomography (CT) has been widely used in medical diagnosis [1][2][3][4] since it was invented in 1973. X-ray CT scans automatically explore the internal structure of the human body.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As high dosage X-rays can be harmful to human body [3,4,5], substantial efforts have been devoted to image reconstruction using low-dose CT measurements [6,7,8]. There are two main strategies for dose reduction in CT scans: one is to reduce the number of views, and the other is to reduce the exposure time and the current of X-ray tube [9], both of which will introduce various degrees of noise and artifacts and then compromise the subsequent diagnosis. Here we focus on the second type however our method is not specific to a particular scanning mode.…”
Section: Introductionmentioning
confidence: 99%